2019
DOI: 10.3389/fonc.2019.00271
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Level of Red Cell Distribution Width as a Prognostic Indicator for Survival in a Large Cohort Study of Male Laryngeal Squamous Carcinoma

Abstract: Objective: High levels of red cell distribution width (RDW) may be associated with adverse outcomes in patients with cancer. The purpose of the present study was to investigate the prognostic impact of pretreatment RDW levels on overall survival (OS), cancer-specific survival (CSS), and disease-free survival (DFS) in a large cohort of male laryngeal squamous cell cancer (LSCC) patients. Methods: A total of 809 LSCC patients who were treated between 2007 and 2011 at the Eye & … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…RDW is conventionally used to evaluate hematological diseases, especially anemia (13). In recent years, RDW has been reported as a biomarker of carcinoma (14)(15)(16)(17). However, the correlation of RDW with bladder cancer is still not clear.…”
Section: Prognostic Significance Of Red Cell Distribution Width In Bladder Cancermentioning
confidence: 99%
“…RDW is conventionally used to evaluate hematological diseases, especially anemia (13). In recent years, RDW has been reported as a biomarker of carcinoma (14)(15)(16)(17). However, the correlation of RDW with bladder cancer is still not clear.…”
Section: Prognostic Significance Of Red Cell Distribution Width In Bladder Cancermentioning
confidence: 99%
“…Moreover, the cut-off values are significantly different. For example, in the aforementioned studies, the authors used the cut-off values of 13.2% [ 24 ] and 15% [ 25 ] for RDW, and 2.32 [ 26 ], 2.2 [ 27 ], 1.81 [ 28 ] and 3.9 [ 29 ] for NLR.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies that have investigated the relationship between pre-treatment RDW and prognosis in various types of cancer 9,11,[15][16][17][18] have consistently reported that RDW could be a useful marker for poor prognosis prediction in patients with cancer. In line with these findings, our study also found that a high pretreatment RDW level is a poor prognostic factor for OS and CSS in patients with prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 25 Meanwhile, the heterogeneity of red blood cell size (high RDW) correlates with inflammation and undernutrition status. 10 , 11 A higher tumor stage can lead to significant systemic inflammation through the secretion of cytokines and release of tumor-degradation products, which, in turn, increases RDW levels. 19 In our study, we also found an association between increased tumor size, advanced tumor stage, and high RDW levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation